Khadra's Journey of Finding Her True Identity Across Different Cultures in Mohja Kahf's The Girl in the Tangerine Scarf - Ikhtiyanti, Ata Amrita; Azzahra, Raissa Putri (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2024)
The novel The Girl in the Tangerine Scarf tells the story of a Muslim woman, Khadra Shamy, living in a non-Muslim country, experiencing various cultural and value clashes. Mohja Kahf, the author of the novel, portrays Khadra's journey in trying to discover her true identity as a Muslim woman. This article discusses the formation of Khadra Shamy’s identity in America. The study applies a descriptive qualitative method using Stuart Hall's theory of identity. The article also takes a feminist approach to examine the issues related to women, as the process of identity formation cannot be separated from her status as a woman. The research findings show that, in her quest to find her true identity, there are barriers to women's rights, such as negative prejudice, stereotypes, the existence of a patriarchal society, and injustice. In her search for identity, she resists through several actions, including divorce, abortion, removing her hijab, and trying photography. The process of forming her identity as both an Arab and American Muslim is influenced by various factors, including the Islamic teachings from her parents, which were strict yet did not limit women’s rights, and photography, which allowed her to capture various objects and made her realize that there are many different perspectives in society.